Impact of West Nile Virus on Bird Populations: Limited Lasting Effects, Evidence for Recovery, and Gaps in Our Understanding of Impacts on Ecosystems. Issue 6 (24th September 2019) - Kilpatrick, A Marm; Wheeler, Sarah S
Abstract: The introduction of West Nile virus to North America in 1999 had profound impacts on human and wildlife health. Here, we review studies of WNV impacts on bird populations and find that overall impacts have been less than initially anticipated, with few species showing sustained changes in population size or demographic rates across multiple regions. This raises four questions: 1) What is the evidence for WNV impact on bird populations and how can we strengthen future analyses? We argue that future studies of WNV impacts should explicitly incorporate temporal variation in WNV transmission intensity, integrate field data with laboratory experimental infection studies, and correct for multiple comparisons. 2) What mechanisms might explain the relatively modest impact of WNV on most bird populations? We suggest that spatial and temporal variation in WNV transmission moderates WNV impacts on species that occur in multiple habitats, some of which provide refugia from infection. 3) Have species recovered from the initial invasion of WNV? We find evidence that many species and populations have recovered from initial WNV impact, but a few have not. 4) Did WNV cause cascading effects on other species and ecosystems? Unfortunately, few studies have examined the cascading effects of WNV population declines, but evidence suggests that some species may have been released from predation or competition. We close by discussing potentially overlooked groups of birds that may have been affected by WNV, and one highlight species, the yellow-billed magpie ( Pica nutalli Audubon, 1837 [Passeriformes: Corvidae]), that appears to have suffered the largest range-wide impact from WNV.